Improvement in germination characteristics in artificially aged seeds of okra (Abelmoschus esculentus) by osmoconditioning - RAJ, DESH; DAHIYA, O S; ARYA, R K; YADAV, ASHOK KUMAR; KUMAR, KULDEEP (The Indian Journal of Agricultural Sciences, 2026)
Okra Abelmoschus esculentus (L.) Moench.] seeds of three cultivars, viz. Arka Anamika, Hisar Unnat and Varsha Uphar were subjected to accelerated ageing (exposed to approximately 100% RH at 40Â±1oC for 72 hr) and were hydro and osmoprimed to find out the ability of priming treatment in the repair of deterioration sustained during ageing. Seed quality parameters like germination percent, seedling length, seedling dry weight, vigour index-I and vigour index-II measured in fresh and accelerated aged seed, whereas germination percent was measured in primed seeds. Overall, accelerated ageing reduced germination, seedling length, seedling dry weight, vigour index-I and vigour index-II in all the varieties. However, priming reduced the deleterious effects of ageing and improved germination in all the varieties. Hydration with GA3 (50 ppm for 6 hr), ascorbic acid (100 ppm for 6 hr), polyethylene glycol (PEG) in combination with hydration (6 hr) with water, thiram (0.25%), GA3 (50 ppm for 6 hr) and ascorbic acid (100 ppm for 6 hr) were proved beneficial for enhancing standard germination significantly. Among all these priming treatments the combination of PEG with GA3 and ascorbic acid were proved better/superior for increasing germination in all the three varieties of okra.